A New Micro-Hydrodynamic Herringbone Bearing Using Slant Groove Depth Arrangements for Performance Enhancement. (18th August 2017) - Lee, Y. T.; Yang, A. S.; Juan, Y. H.; Liu, C. S.; Chang, Y. H.
Abstract : This study presents a new groove profile using the slant groove depth arrangements to enhance the performance of micro-HGJBs. The computational analysis was based on the steady-state three-dimensional conservation equations of mass and momentum in conjunction with the cavitation model to examine the complex lubricated flow field. The simulated results of load capacity and circumferential pressure distribution of lubricant film are in good agreement with the measurement data and the predictions cited in the literature. Numerical experiments were extended to determine the pressure distribution, load capacity, radial stiffness and friction torque by varying the slant ratio of groove depth, eccentricity ratio, rotational speed and attitude angle. The cavitation extent of lubricant film was also studied for different slant groove patterns.